2019
DOI: 10.1097/md.0000000000015288
|View full text |Cite
|
Sign up to set email alerts
|

Extradural anterior clinoidectomy and aneurysm clipping using transcranial neuroendoscopic approach

Abstract: Rationale:Anterior clinoidectomy is an important technique for neurovascular and skull base surgery. Until now, extradural anterior clinoidectomies have been performed under a microscope in almost all clinical cases, with only one clinical case performed an extradural pathological anterior clinoid process resection using neuroendoscopy. Additionally, no normal ACP resections have been performed extradurally via neuroendoscopy, especially for aneurysms. We tried to perform extradural anterior clinoidectomies by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Transcranial neuroendoscopic is a minimally invasive surgery and a promising alternative to traditional surgery. It has the advantages of good light, multi angle view, close observation and so on, while has great advantages in hypertensive intracerebral hemorrhage surgery 2 , craniotomy aneurysm clipping surgery 3 , 4 , trigeminal nerve/facial nerve microvascular decompression surgery 6 , and even craniotomy brain tumor surgery. Study 10 has shown that transcranial neuroendoscopic is more than 90% of hematoma removal in intracerebral hemorrhage surgery.…”
Section: Discussmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial neuroendoscopic is a minimally invasive surgery and a promising alternative to traditional surgery. It has the advantages of good light, multi angle view, close observation and so on, while has great advantages in hypertensive intracerebral hemorrhage surgery 2 , craniotomy aneurysm clipping surgery 3 , 4 , trigeminal nerve/facial nerve microvascular decompression surgery 6 , and even craniotomy brain tumor surgery. Study 10 has shown that transcranial neuroendoscopic is more than 90% of hematoma removal in intracerebral hemorrhage surgery.…”
Section: Discussmentioning
confidence: 99%
“…combined with 3D printing technology can truly restore the shape and location of intracranial lesions, which is not only of great help to anatomy-based neurosurgery, but also can accurately locate intracranial lesions through 3D printing guide 1 , effectively avoiding unnecessary nerve damage. In recent years, the creative use of transcranial neuroendoscopic in the operations of intracerebral hemorrhage, intracranial tumors, intracranial aneurysms, arteriovenous malformations, and trigeminal/facial nerve microvascular decompression has brought the minimally invasive surgery of neurosurgery to a new level [2][3][4][5][6] . In this clinical study, through 3D-Slicer preoperative reconstruction of intracranial lesions and accurate preoperative positioning with 3D printing guide, the intracranial lesions can be accurately located, and the most reasonable surgical approach can be planned without intraoperative neuronavigational system.…”
mentioning
confidence: 99%
“…15 Whether to perform a clinoidectomy intradurally or extradurally can be influenced by anatomic factors and surgeon preference. 15,16 In this operative video, the anterior clinoid process is seen to obscure part of the PCOM aneurysm and the site for proximal carotid artery control. 6 Clinoidectomy combined with opening of the opticocarotid cistern allowed for proximal control and visualization of the posterior communicating artery.…”
mentioning
confidence: 94%
“…6 Occasionally, the anterior choroidal artery may be stuck to the dome and must be dissected free. 15,16 As the authors have demonstrated, full visualization of the vascular anatomy in this region is vital to ensure safe clipping. Exquisite care must be taken in positioning and closing of the aneurysm clip to prevent compromise of the parent arteries.…”
mentioning
confidence: 99%
“…To date, most cases of HS have been treated under microscopy. However, there has been a gradual increase in the number of cases treated by neuroendoscopy due to its advantages of excellent illumination, clear visualization, and multiangle views 6 10 . In this report, we present our preliminary experience with a transcranial neuroendoscopic approach in the treatment of HS.…”
Section: Introductionmentioning
confidence: 99%